2022
DOI: 10.1039/d1cp03898b
|View full text |Cite
|
Sign up to set email alerts
|

Integrating trace amounts of Pd nanoparticles into Mo3N2 nanobelts for an improved hydrogen evolution reaction

Abstract: Significant efforts have been directed towards the use of transition metal nitrides as electrocatalysts for hydrogen evolution reaction (HER). Molybdenum nitride, despite its promise for scalable production, suffers from the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…[42] Mo 3 N 2 has metallic characteristics, which is reported in literatures. [43,44] The difference in the work function suggests that there would be band alignments and self-driven electron transfer from Mo 3 N 2 to MoO 2 at their coupling heterointerfaces during contact until the work function equilibrium is reached. As the corresponding schematic energy band diagrams illustrated in Figure 5e, a spontaneous BIEF pointing toward the MoO 2 side can be formed when the metallic Mo 3 N 2 and semiconducting MoO 2 are in contact.…”
Section: Buffer Mechanism Of Gmm Interfacial Layermentioning
confidence: 99%
“…[42] Mo 3 N 2 has metallic characteristics, which is reported in literatures. [43,44] The difference in the work function suggests that there would be band alignments and self-driven electron transfer from Mo 3 N 2 to MoO 2 at their coupling heterointerfaces during contact until the work function equilibrium is reached. As the corresponding schematic energy band diagrams illustrated in Figure 5e, a spontaneous BIEF pointing toward the MoO 2 side can be formed when the metallic Mo 3 N 2 and semiconducting MoO 2 are in contact.…”
Section: Buffer Mechanism Of Gmm Interfacial Layermentioning
confidence: 99%
“…Transition metal carbides (TMCs), transition metal phosphides (TMPs), transition metal borides (TMBs), and transition metal nitrides (TMNs) have been explored as electrocatalysts for the HER. 38–62 Abghoui et al 54 reported that TaN, HfN, MoN, and ScN catalyze the HER at overpotentials between −0.09 V and −0.34 V. Peterson et al 63 demonstrated that the activity of TMC catalysts is between low activities shown by early transition metals and high activities shown by compounds of Pt/Pt-group metals. In addition to the above, TMPs have also been explored as potential catalysts for the HER, including the phosphides of Co, Ni, and Fe.…”
Section: Introductionmentioning
confidence: 99%
“…The other method is to obtain a moderate binding strength for Pd through the strong interaction between the catalyst and support by means of the functional support (synergistic and ligand effects), so as to improve its hydrogen precipitation activity. These supports include CoS 2 , 26 MoS 2 , 27,28 VS 2 , 29 NiCo 2 S 4 , 30 Mo 3 N 2 , 31 MoO 3 , 32 TiO 2 , 33 FeOx (OH) 2 , 6 Co/CoO x , 34 graphene, 14,21,35,36 and graphitized carbon nanofibers. 37 Last, the most important way is to synthesize Pdbased alloys, and to change the hydrogen adsorption energy on their surfaces through the electronic effect between the alloys, which is the key parameter for HER.…”
Section: Introductionmentioning
confidence: 99%